Ependymal lined paraventricular cerebral cysts; a report of three cases. Issue 4 (August 1973) - Bouch, D. C.; Mitchell, I.; Maloney, A. F. J.
Abstract : Three cases are reported, each with a benign ependymal-lined cyst which produced clinical signs and symptoms simulating cerebrovascular disease or cerebral neoplasm. The pathological features are described and their histogenesis discussed.